2014
DOI: 10.1245/s10434-013-3464-x
|View full text |Cite
|
Sign up to set email alerts
|

Age as a Predictor of Sentinel Node Metastasis among Patients with Localized Melanoma: An Inverse Correlation of Melanoma Mortality and Incidence of Sentinel Node Metastasis Among Young and Old Patients

Abstract: Purpose We have previously reported that older patients with clinical Stage I and II primary cutaneous. melanoma had lower survival rates compared to younger patients We postulated that the incidence of nodal metastasis would therefore be higher among older melanoma patients. Materials and Methods The expanded AJCC Melanoma Staging Database contains a cohort of 7756 melanoma patients who presented without clinical evidence of regional lymph node or distant metastasis and who underwent a sentinel node biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 47 publications
(34 reference statements)
8
81
1
6
Order By: Relevance
“…Various melanoma studies have demonstrated that patient age is an independent prognostic factor for survival (3)(4)(5)(6). It has been established in patients with early stage primary melanoma that older patients have more unfavorable clinicopathological features, such as the melanoma is thicker, ulcerated and has a higher mitotic rate (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various melanoma studies have demonstrated that patient age is an independent prognostic factor for survival (3)(4)(5)(6). It has been established in patients with early stage primary melanoma that older patients have more unfavorable clinicopathological features, such as the melanoma is thicker, ulcerated and has a higher mitotic rate (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established in patients with early stage primary melanoma that older patients have more unfavorable clinicopathological features, such as the melanoma is thicker, ulcerated and has a higher mitotic rate (3)(4)(5)(6). A large analysis of 17,600 patients with melanoma demonstrated that older patients had more advanced primary tumors, and that older age was correlated with lower melanoma survival (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations